Haiti : Sixth Review Under the Extended Credit Facility, Request for Waiver of Performance Criterion, and Augmentation of Access; Staff Report; Staff Statements; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Haiti. (IMF Staff Country Reports; Country Report, 2010)
This paper presents Haiti's Sixth Review under the Extended Credit Facility and request for Waiver of Performance Criterion, and Augmentation of Access. Manufacturing activity would be hit the most, as the largest enterprises, including the important export textile sector, have been located in the Port-au-Prince area. The destruction of government and private buildings is also estimated to result in a sharp drop in government services, commerce, and tourism. Agriculture, the main growth driver, would be affected owing to widespread damages to the production systems in and around the earthquake area.